2022
DOI: 10.1038/s41598-022-05326-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing differences in surgical outcomes following emergency abdominal exploration for complications of elective surgery and high-risk primary emergencies

Abstract: Irrespective of its etiology, emergency surgical abdominal exploration (EAE) is considered a high-risk procedure with mortality rates exceeding 20%. The aim of this study was to evaluate differences in outcomes in patients who required EAE due to complications of complex elective abdominal procedures and those who required EAE due to high-risk primary abdominal emergencies. Patients undergoing EAE for acute surgical complications of complex abdominal elective surgical procedures (N = 293; Elective group) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
3
4
0
2
Order By: Relevance
“…We were able to demonstrate that only emergency surgery was significantly associated with poorer OS (HR 2.68, 95% CI 1.32-5.05, p = 0.003). This is in line with previously published studies which show that emergency abdominal surgery generally shows higher postoperative mortality rates (25,26). Additionally, a study focusing on emergency gastric surgery found in-hospital mortality rates of up to 50% (27).…”
Section: Discussionsupporting
confidence: 92%
“…We were able to demonstrate that only emergency surgery was significantly associated with poorer OS (HR 2.68, 95% CI 1.32-5.05, p = 0.003). This is in line with previously published studies which show that emergency abdominal surgery generally shows higher postoperative mortality rates (25,26). Additionally, a study focusing on emergency gastric surgery found in-hospital mortality rates of up to 50% (27).…”
Section: Discussionsupporting
confidence: 92%
“…This preoperative assessment was associated with potentially reducing the risk of postoperative complications. However, the study also underscored the relatively low complication burden in the elective group, juxtaposed with markedly high mortality rates, reflecting the intrinsically high-risk nature of abdominal events [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…De remarcat că mortalitatea celor operanți în urgență a fost sensibil mai mare,11/17 (64,70%),constatare care era previzibilă, prezentă și în alte publicații (33,34). Operații laparoscopice au fost 9 (29,45%) cu 4 decese.…”
Section: Discuțiiunclassified
“…S-au adăugat și erorile latente, de sistem. După clasificarea Leape, majoritatea erorilor au fost de 33 Nicolau AE Erori chirurgicale-expertiza contestatiilor 34 diagnostic, 3 și de PTE 3,doar o eroare de tehnică operatorie, iar în toate cazurile s-au sumat și erori de sistem. Un articol de referință, care se bazează pe definiția complicației post operării utilizată în Olanda, analizează evoluția a 12.121 de pacienți internați în secția de chirurgie.…”
Section: Discuțiiunclassified